AKTIVITAS MASYARAKAT DAN KULINER JAJANAN PASAR KHAS SOLO SEBAGAI SUMBER IDE PENCIPTAAN DESAIN TEKSTIL - Senja Ari Nur Dewanti; Darwoto Darwoto (Narada : Jurnal Desain dan Seni, 2021)
The background of designing this product is to create innovation in visual textile design, especially for surface design with traditional Solo traditional food visuals (Jajan pasar) which is contained in the atmosphere where the food is located with the intention of conveying a message so that the millennial generation knows more and wants to preserve something traditional. , and it can be started from the most common thing, namely getting to know traditional food from Solo. This work will later explore the form of traditional food, especially Solo traditional snacks and the atmosphere where the food is located which will be visualized into designs on the textile surface. This work comes because of the problem of traditional food which is now being displaced by external foods such as junk food, fast food, and western food. Apart from that, the modernization style of the teenagers is arguably westernized which also affects their diet in their daily interactions. In order to support their existence and match the lifestyle of other friends. The results of this design can be concluded into a number of things: (1) exploring the visual form of digital design with the source of the idea of "Typical Solo Market Jajanan Pasar" with illustrative styling with food visuals that resemble its original form in which a selling and buying story is written, as well as placing objects food itself into people's daily lives. (2) The design is intended for media promotion of typical Solo food to adolescents. (3) The design is realized with digital printing techniques which will later be transformed into unisex clothing for ages 17-25 years (late teens). In addition, this product is expected to convey a message and can be a special attraction for millennial generation children to preserve and love something traditional, as well as a new style campaign in maintaining the existence of something that is traditional and is one of the cultures, namely by making this product. as a souvenir which will later be processed into clothing products favored by millennial children.